A case-based Windows graphic package for the education and training of power system restoration. - Islam, S. (IEEE Transactions on power systems)
This paper presents a case-based Windows graphic package developed by the authors for the education and training of power system restoration. In order to overcome the inherent complexities associated with a restoration switching sequence, a case-based reasoning (CBR) algorithm has been developed. An object-oriented Windows-based graphical user interface (GUI) has been developed to communicate with the expert system and to visualize outputs. Simulation results on a part of the Saskatchewan Power (SaskPower) network have been presented in this paper. The restoration practices of SaskPower network have been collected and stored in a knowledge database called case library. The power flow and the implementation risk analysis tools have been incorporated into the expert system. A risk analysis tool has been used to determine the implementation risk due to the imperfect switching actions. Using the GUI, a user can simulate a blackout event on the system under study. The expert system proposes a restoration proposal after reasoning with the past solutions available in the case library. Using the power flow analysis tool, the user can check the system scenarios after the restoration proposal is implemented